S27 Should routine screening for vitamin d deficiency be incorporated into current guidelines for treatment of paediatric TB patients?. (16th November 2010) - Ting, A; Jiki, M; Bell, C; Murray, C; Mughal, Z; Child, F
Abstract : Introduction and Objectives: The association between low vitamin D levels and increased severity/susceptibility to TB infection due to suppression of innate immunity is well known. In the United Kingdom, low levels of background ultraviolet B radiation limit the photoconversion of 7 dehydrocholestrol in skin to cholecalciferol (vitamin D3). In addition the majority of paediatric TB cases in the UK occur in non-Caucasian patients who by nature of their skin colour are less able to absorb the UV radiation. Current guidelines do not suggest routine checking of serum 25-dihydroxyvitamin D (25(OH)D); a reliable measure of body stores of vitamin D, in paediatric TB cases and providing Vitamin D supplementation as required. We hypothesised that all paediatric TB patients require screening for Vitamin D deficiency and that many would benefit from supplementation. Methods: This is a prospective cohort study. Between January 2009 and June 2010, all paediatric TB cases were prospectively recorded into a hospital database. Data collected include age, sex, serum concentrations of 25(OH)D, calcium (Ca), phosphate (P), alkaline phosphatase (ALP) and parathyroid hormone (PTH). Results: 45 patients (18 males) were diagnosed with TB over the 18 month period. The mean age was 7.5 years (range 5 months to 17 years). The results for Vitamin D were not available in 5 patients (3 in progress, 2 not performed). Of the 40 patients with results available, 39 (97.5%) were found to have low levels of 25 (OH)D and were commenced on supplementation. Of these, 29/40 (72.5%) had profound Vitamin D deficiency (25(OH)D levels <10 ng/ml). Of these 29 patients, 15 had high PTH levels, 2 had low Ca (no data for one patient), 4 had low P levels and 5 had elevated ALP levels. One patient had radiologically confirmed rickets. Conclusions: Our study supports the incorporation of routine Vitamin D screening into the current guidelines for the management of TB, especially as TB itself can worsen pre-existing vitamin D deficiency.